Synchronization of the unified chaotic systems via active control - Uçar, A; Lonngren, KE; Bai, EW (Pergamon-Elsevier Science Ltd, 2006)
This paper investigates the synchronization of coupled unified chaotic systems via active control. The synchronization is given in the slave-master scheme and the controller ensures that the states of the controlled chaotic slave system exponentially synchronize with the state of the master system. Numerical simulations are provided for illustration and verification of the proposed method. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Lorenz; Dynamics